北极地区的合作与竞争研究 - Marc-Albert Bohemier (2012)
近年来，越来越多的学者和媒体开始关注北极附近的国家之间争夺北极海域的石油和天然气资源的问题。北极冰山的日渐融化，使得进入北极海域油气资源的认可开采区、甚至是未认可开采区都更加便利。而新型科学技术的推广，则极大地减轻了北极恶劣气候对开采油气资源造成的不便。目前，加拿大、挪威、丹麦、美国和俄罗斯——即北极五国——正在激烈争论北极新融化海域的划界问题。同时，这些国家还相继出台了加强北极海域国防的政策。本文重点分析了北极油气资源开发的现状、有关国界划分的国际法、各国在北极地区的国防政策以及北极五国的国际军事关系等方面的问题。通过分析探讨得出结论：未来各国间关于北极油气资源的争夺战会逐渐缓和。究其原因，. Many articles in the popular press suggest that there is a combative race between the five Arctic coastal states for the Arctic oil and gas. Indeed, the Arctic ice cap is melting, which facilitates the access to the huge proved and undiscovered oil and gas in the Arctic. New technology allows drilling in the harsh environment of the Arctic. Canada, Norway, Denmark, the United States and Russia – t. 学位：法学硕士 院系专业：南洋研究院_国际关系 学号：30220101154356